Environmentally friendly wet casting clay sand and preparation method thereof

By adding chaff powder, potassium acetate and rare earth oxide powder to the wet cast clay sand, the environmental pollution and mechanical properties of traditional coal pulverized clay sand casting are solved, and the production and environmental protection goals of high-quality ductile iron parts are achieved.

CN119237655BActive Publication Date: 2025-04-08SHANDONG XUGUANG DERUI NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411783839.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-08
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Traditional coal pulverized clay sand casting has serious environmental pollution and deterioration of labor conditions, and ductile iron parts often have sheet-like graphite surface layers, which affects the mechanical properties.

Method used

The environmentally friendly and moisturizing cast clay sand is used without adding coal powder. By adding chaff powder, potassium acetate and rare earth oxide powder, the sheet-like graphite layer of ductile iron parts is eliminated, and the thermal and moisture tensile strength and sand resistance of the molded sand are improved.

Benefits of technology

The production of high-quality ductile iron parts has been achieved, the emission of waste sand and waste gas during the casting process has been reduced, and the labor conditions and environmental sanitation have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application discloses a kind of environmentally friendly wet casting clay sand and its preparation method, and belongs to the technical field of casting modeling materials. It includes the following components in mass percentage: sodium bentonite 5-8wt%, α-starch 0.2-1.5wt%, husk powder 0.5-1.5wt%, potassium acetate 0.1-0.4wt%, red mud 0.1-0.2w%, rare earth oxide powder 0.1-0.5wt%, ethyl silicate 0.1-1wt%, water 2.7-3.5wt%, and the rest is silica sand. No coal powder is added to the sand, and the flaky graphite layer of ductile iron castings is eliminated through the synergistic effect of each component, and the adhesion ability of clay colloid and the strength of molding sand are improved, not only can high-quality ductile iron castings be obtained, but also waste sand and waste gas emissions can be reduced during casting, and the requirements of energy reduction, emission reduction, quality improvement and efficiency increase are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an environmentally friendly wet mold casting clay sand and a preparation method thereof, belonging to the technical field of casting molding materials. Background Art

[0002] At present, coal powder clay sand casting is widely used at home and abroad. Adding coal powder to the sand can prevent mechanical sand sticking to the casting and make the surface of the casting smooth and beautiful. However, coal powder seriously deteriorates working conditions and environmental hygiene. Coal powder also emits an unpleasant odor and a lot of thick smoke during pouring. The smoke contains a large amount of harmful gases such as dioxins, which are very harmful to the human body. The amount of new sand, bentonite and coal powder added to coal powder clay sand is large, the reuse rate of old sand is low, and the amount of waste sand discharged is large. It is difficult for traditional casting sand to meet the requirements of emission and energy saving.

[0003] my country's casting output accounts for more than 50% of the world's casting output. The output of ductile iron has basically increased year by year, currently accounting for 30% of the casting output, of which most small and medium-sized parts are cast using wet clay sand. Ductile iron parts cast using wet clay sand often have a flaky graphite surface layer. Since the mechanical properties of ductile iron mainly depend on the shape of graphite, the presence of flaky graphite defects on the surface layer of ductile iron parts will lead to poor mechanical properties. Summary of the invention

[0004] In order to solve the above problems, the present invention provides an environmentally friendly wet casting clay sand and a preparation method thereof. No coal powder is added to the sand, and flaky graphite layers of ductile iron parts are eliminated by adding husk powder, potassium acetate and rare earth oxide powder. Not only high-quality ductile iron parts can be obtained, but also waste sand and exhaust gas emissions during the casting process can be reduced.

[0005] According to one aspect of the present application, an environmentally friendly wet casting clay sand is provided, comprising the following components in percentage by mass: 5-8wt% sodium bentonite, 0.2-1.5wt% α-starch, 0.5-1.5wt% rice husk powder, 0.1-0.4wt% potassium acetate, 0.1-0.2w% red mud, 0.1-0.5wt% rare earth oxide powder, 0.1-1wt% ethyl silicate, 2.7-3.5wt% water, and the rest being silica sand.

[0006] α-starch can not only improve the hot wet tensile strength of the molding sand, but also produce gaps on the surface of the mold after burning, which can buffer the thermal expansion of silica sand and greatly improve the ability of the molding sand to resist sand inclusion. At the same time, α-starch can also reduce the friction between the molding sand and the mold, and improve the mold release of the molding sand; it can significantly reduce the sensitivity of wet molding sand to moisture, reduce the water content of molding sand and increase the compaction rate of molding sand, improve the ability of molding sand to resist wind drying, and reduce sand holes and surface roughness defects in castings.

[0007] Husk powder is rich in cellulose, lignin, and silica, and has good toughness and porosity. It can improve the hot and wet tensile strength of the molding sand. After burning, the husk powder produces reducing gas, which can prevent the casting from sticking sand. Husk powder has good water retention and porosity, and can filter and absorb the smoke generated during pouring. It can also buffer the thermal expansion of silica sand, greatly improving the ability of the molding sand to resist sand inclusion.

[0008] The main components of rare earth oxide powder are La2O3 and CeO2. The synergistic effect between nano La2O3 and CeO2 particles and bentonite particles increases the contact surface of bentonite flocculants and greatly improves the adhesion ability of clay colloids. Nano La2O3 and CeO2 particles can also improve the dispersion properties of α-starch and increase the strength uniformity of molding sand.

[0009] Preferably, the molding sand comprises the following components in percentage by mass: 5.5-7wt% sodium bentonite, 0.6-1wt% α-starch, 1.0-1.3wt% rice husk powder, 0.20-0.35wt% potassium acetate, 0.15-0.2w% red mud, 0.1-0.4wt% rare earth oxide powder, 0.2-0.6wt% ethyl silicate, 2.7-3wt% water, and the rest is silica sand.

[0010] Preferably, more than 95wt% of the red mud passes through a 200-mesh sieve, and the red mud comprises the following components in percentage by mass: 3-20wt% SiO2, 2-8wt% CaO, 10-20wt% Al2O3, 3-10wt% Na2O, and the rest are other oxides.

[0011] Preferably, more than 95 wt% of the sodium bentonite passes through a 200-mesh sieve, and the colloid value is greater than 99 mL / 15 g.

[0012] Preferably, more than 95 wt% of the α-starch passes through a 100-mesh sieve, and the degree of gelatinization is greater than 96%.

[0013] Preferably, more than 95wt% of the husk powder passes through a 140-mesh sieve, and the organic matter in the husk powder is greater than 80wt%; the organic matter in the husk powder can improve the structure of the molding sand through structural stability and cementation, increase the compressive strength and shear strength of the molding sand, and improve the ability of the molding sand to resist erosion by molten iron.

[0014] Preferably, more than 95wt% of the mass of the potassium acetate passes through a 100-mesh sieve, and the purity of the potassium acetate is greater than 95wt%. The addition of potassium acetate can not only improve the activity of bentonite, but also decompose to produce CO2, thereby reducing the surface roughness and sand adhesion defects of the casting. At the same time, potassium acetate has a cleaning effect on the surface of silica sand and improves the adhesion ability of the binder on the sand particles. High-purity potassium acetate can prevent other substances from reducing the bonding ability of bentonite.

[0015] Preferably, more than 95 wt% of the mass of the rare earth oxide powder passes through a 200 mesh sieve, including La2O3 and / or CeO2.

[0016] Preferably, the purity of the ethyl silicate is greater than 99%, and the ethyl silicate may be one or more of ethyl silicate 28, ethyl silicate 32 or ethyl silicate 40.

[0017] According to another aspect of the present application, a method for preparing environmentally friendly green casting clay sand is provided, comprising the following steps:

[0018] a1. Add potassium acetate to water and stir to dissolve it; then add ethyl silicate and stir to obtain ethyl silicate hydrolyzate;

[0019] a2. Add ethyl silicate hydrolyzate to silica sand and premix;

[0020] a3. Add red mud, rare earth oxide powder and husk powder to the premix;

[0021] a4. Then, sodium bentonite and α-starch are added to the mixture and mixed thoroughly to obtain the environmentally friendly wet mold casting clay sand. Compared with first mixing the particles and then adding them to the liquid phase system, directly adding the solid component materials to the ethyl silicate aqueous solution in sequence can effectively reduce the flying of dust, reduce the risk of dust explosion, and improve the safety and sanitation quality of the production environment.

[0022] Optionally, in step a1, the stirring process of potassium acetate dissolution is 50-120 seconds; and the stirring process of ethyl silicate hydrolysis is 60-80 minutes.

[0023] Optionally, the premixing time in step a2 is 5-15 s, the mixing time in step a3 is 5-15 s, and the mixing time in step a4 is 60-120 s.

[0024] According to another aspect of the present application, a method for preparing environmentally friendly green casting clay sand is provided, comprising the following steps:

[0025] b1. Add potassium acetate to water and stir to dissolve it; then add ethyl silicate and stir to obtain ethyl silicate hydrolyzate;

[0026] b2. Mix red mud, rare earth oxide powder, rice husk powder, sodium bentonite, α-starch and silica sand;

[0027] b3. Add the ethyl silicate hydrolyzate prepared in b1. and mix them to obtain the environmentally friendly wet mold casting clay sand.

[0028] Optionally, in step b1, the stirring process of potassium acetate dissolution is 50-120 seconds; and the stirring process of ethyl silicate hydrolysis is 60-80 minutes.

[0029] Optionally, the mixing time in step b2 is 15-30 s, and the mixing time in step b3 is 60-120 s.

[0030] The beneficial effects of this application include but are not limited to:

[0031] 1. According to the environmentally friendly wet casting clay sand provided in this application, the casting process reduces the emission of waste sand and waste gas, is green and environmentally friendly, and saves energy and reduces emissions; sodium bentonite and ethyl silicate work synergistically to improve the bonding ability of clay; the addition of rice husk powder and starch improves the strength and stability of the molding sand; through the reasonable proportion of each component, the prepared molding sand has excellent performance, the casting produced by the molding sand is easy to demold, and the surface finish and yield rate of the produced castings are both high.

[0032] 2. According to the environmentally friendly wet casting clay sand provided by the present application, rice husk powder is added. When the rice husk is heated by high-temperature molten iron, the ash contains amorphous silicon with many pores, which can slow down the inoculation decay of the surface layer of the ductile iron parts.

[0033] 3. According to the environmentally friendly wet casting clay sand provided by the present application, by adding rare earth oxide powder, the main components of which are La2O3 and CeO2, the La2O3 and CeO2 powders can not only react with the sulfur on the surface of the molten iron to form sulfur oxides, but also absorb the sulfur dioxide generated during pouring, which can not only prevent the spherical graphite in the molten iron from turning into flakes due to the reduction of magnesium content in the molten iron by sulfur, but also prevent the overflow of sulfur dioxide.

[0034] 4. According to the environmentally friendly wet mold casting clay sand provided by the present application, red mud powder is added therein. The red mud is rich in alkaline substances such as Na2O and CaO, which can not only react with the sulfur in the molding sand to eliminate the possibility of the spherical graphite being transformed into flakes by sulfur, but also can be used to absorb gases such as CO, SO2, and CO2, desulfurize and fix carbon, and reduce gas emissions. Al2O3 in the red mud can eliminate sand sticking on the surface of the casting.

[0035] 5. According to the environmentally friendly wet casting clay sand provided by the present application, potassium acetate is added therein, which can promote the hydrolysis of ethyl silicate. Potassium acetate not only improves the activity of bentonite, but also reacts with sulfur in the surface layer of molten metal and auxiliary materials to prevent sulfur from reacting with magnesium in molten iron, which is beneficial to reducing or eliminating the flaky graphite layer on the surface of ductile iron parts. The CO2 generated by the thermal decomposition of potassium acetate reduces the surface roughness and sand adhesion defects of castings. DETAILED DESCRIPTION

[0036] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0037] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in this scheme are for demonstration purposes only.

[0038] Components used in the embodiments and comparative examples:

[0039] Sodium bentonite, red mud, and rare earth oxides all passed through a 200-mesh sieve; rice husk powder passed through a 140-mesh sieve; and α-starch and potassium acetate passed through a 100-mesh sieve.

[0040] Among them, the organic matter content in the husk powder is greater than the colloid value is greater than 80wt%; the colloid value of sodium bentonite is greater than 99mL / 15g; more than 95wt% of the mass of α-starch passes through a 100-mesh sieve, and the gelatinization degree is greater than 96%; the purity of potassium acetate is greater than 95wt%.

[0041] In Examples 1-7 and the comparative examples, the ethyl silicate is ethyl silicate 28, and the SiO2 content is 28-30wt%.

[0042] The preparation methods used in Examples 3-5 are the same as those in Example 2.

[0043] Example 1

[0044] Molding sand 1# includes the following components in parts by mass: 5 parts of sodium bentonite, 1.5 parts of α-starch, 1.5 parts of rice husk powder, 0.4 parts of potassium acetate, 0.2 parts of red mud, 0.5 parts of rare earth oxide powder (La2O3:CeO2=1), 1 part of ethyl silicate (SiO2 is 28-30wt%), 3.5 parts of water, and the rest is silica sand.

[0045] The environmentally friendly wet casting clay sand is prepared by the following method:

[0046] b1. Add potassium acetate to water and stir for 50 seconds to dissolve it; then add ethyl silicate and stir for 60 minutes to obtain ethyl silicate hydrolyzate;

[0047] b2. Add red mud, rare earth oxide powder, rice husk powder, sodium bentonite, α-starch and silica sand into a sand mixer and stir for 30 seconds until uniform;

[0048] b3. Add the ethyl silicate hydrolyzate prepared in b1. and mix in a sand mixer for 10-30 seconds to obtain molding sand 1#.

[0049] Example 2

[0050] Molding sand 2# includes the following components in parts by mass: 5 parts of sodium bentonite, 1.5 parts of α-starch, 1.5 parts of rice husk powder, 0.4 parts of potassium acetate, 0.2 parts of red mud, 0.5 parts of rare earth oxide powder (La2O3:CeO2=1), 1 part of ethyl silicate, 2.7 parts of water, and the rest is silica sand.

[0051] The environmentally friendly wet casting clay sand is prepared by the following method:

[0052] a1. Add potassium acetate to water and stir for 50 seconds to dissolve it; then add ethyl silicate and stir for 1 hour to obtain ethyl silicate hydrolyzate;

[0053] a2. Add ethyl silicate hydrolyzate to silica sand and premix in a sand mixer for 10 seconds;

[0054] a3. Add red mud, rare earth oxide powder and husk powder to the premix and mix for 10 seconds;

[0055] a4. Add sodium bentonite and α-starch into the mixture and mix thoroughly for 120 seconds to obtain molding sand 2#.

[0056] Example 3

[0057] Molding sand 3# includes the following components in parts by mass: 8 parts of sodium bentonite, 0.2 parts of α-starch, 0.5 parts of rice husk powder, 0.1 parts of potassium acetate, 0.1 parts of red mud, 0.1 parts of rare earth oxide powder (La2O3:CeO2=1), 0.1 parts of ethyl silicate, 3.8 parts of water, and the rest is silica sand.

[0058] Example 4

[0059] Molding sand 4# includes the following components in parts by mass: 8 parts of sodium bentonite, 0.2 parts of α-starch, 0.5 parts of rice husk powder, 0.1 parts of potassium acetate, 0.1 parts of red mud, 0.1 parts of rare earth oxide powder (La2O3:CeO2=1), 0.1 parts of ethyl silicate, 2.7 parts of water, and the rest is silica sand.

[0060] Example 5

[0061] Molding sand 5# includes the following components in parts by mass: 6.5 parts of sodium bentonite, 0.8 parts of α-starch, 1.0 parts of rice husk powder, 0.25 parts of potassium acetate, 0.15 parts of red mud, 0.3 parts of rare earth oxide powder (La2O3:CeO2=1), 0.5 parts of ethyl silicate, 3 parts of water, and the rest is silica sand.

[0062] Example 6

[0063] The difference between Example 6 and Example 5 is that in 0.3 parts of rare earth oxide powder in molding sand 6#, La2O3:CeO2=1:9.

[0064] Example 7

[0065] The difference between Example 7 and Example 5 is that 0.3 parts of rare earth oxide powder in molding sand 7# contains Pr6O 11 :CeO2=1:1.

[0066] Example 8

[0067] The difference between Example 8 and Example 5 is that the SiO2 content in the ethyl silicate in the molding sand 8# is 40-42wt%.

[0068] Comparative Example 1

[0069] The difference between Comparative Example 1 and Example 5 is that the molding sand D1# includes the following components in parts by mass: 87.7 parts of silica sand, 6.5 parts of sodium bentonite, 2.8 parts of coal powder, and 3 parts of water.

[0070] Comparative Example 2

[0071] The difference between Comparative Example 2 and Example 5 is that the molding sand D2# does not include red mud.

[0072] Comparative Example 3

[0073] The difference between Comparative Example 3 and Example 5 is that the molding sand D3# does not include rice husk powder.

[0074] Comparative Example 4

[0075] The difference between Comparative Example 4 and Example 5 is that the molding sand D4# does not include α-starch.

[0076] Test example

[0077] The properties of the environmentally friendly wet casting clay sands of Examples 1-8 and Comparative Examples 2-3 and the coal powder clay sand of Comparative Example 1 were tested respectively, and the results are shown in Table 1.

[0078] Table 1

[0079]

[0080] It can be seen from Table 1 that compared with the coal powder clay molding sand of Comparative Example 1, the compaction rate, strength, air permeability and casting performance of the environmentally friendly wet casting clay molding sand of Examples 1-5 are better, so that the surface finish of the castings produced by the molding sand is high, the air permeability is increased while ensuring the strength of the molding sand, the porosity defects of the castings are reduced, and the qualified rate of the finished products is increased.

[0081] Application Example 1

[0082] The ductile iron castings were cast after molding using the molding sand 5# of Example 5 and the comparative molding sand 1# of Comparative Example 1, and the smoke emission during the casting was measured respectively:

[0083] For the casting mold made of molding sand 1#, the smoke dust emission per kilogram of molding sand is 1667 mg; for the casting mold made of molding sand 5#, the smoke dust emission per kilogram of molding sand is 662 mg; after 6 months of repeated use, a large amount of waste sand is generated in molding sand 1#, and the same mass of new sand needs to be added, while there is no waste sand emission in molding sand 5#, and no new sand needs to be added.

[0084] Application Example 2

[0085] 87 kg of three-way ductile iron castings were produced using the molding sand 5# of Example 5 and the comparative molding sand 1# of Comparative Example 1. Samples were taken once a month. The conditions of the flaky graphite layer on the surface of the ductile iron castings are shown in Table 2.

[0086] Table 2

[0087]

[0088] It can be seen from Table 2 that the use of the casting sand 5# can significantly eliminate the flaky graphite layer on the surface of the ductile iron casting.

[0089] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.

Claims

1. An environmentally friendly wet casting clay sand, characterized in that: The invention comprises the following components in percentage by weight: 5-8wt% sodium bentonite, 0.2-1.5wt% alpha-starch, 0.5-1.5wt% rice husk powder, 0.1-0.4wt% potassium acetate, 0.1-0.2wt% red mud, 0.1-0.5wt% rare earth oxide powder, 0.1-1wt% ethyl silicate, 2.7-3.5wt% water, and the rest is silica sand.

2. The environmentally friendly green casting clay sand according to claim 1, characterized in that: The invention comprises the following components in percentage by weight: 5.5-7wt% sodium bentonite, 0.6-1wt% alpha-starch, 1.0-1.3wt% rice husk powder, 0.20-0.35wt% potassium acetate, 0.15-0.2wt% red mud, 0.1-0.4wt% rare earth oxide powder, 0.2-0.6wt% ethyl silicate, 2.7-3wt% water, and the rest is silica sand.

3. The environmentally friendly green casting clay sand according to claim 2, characterized in that: The particle size of red mud is less than 200 mesh.

4. The environmentally friendly green casting clay sand according to claim 3, characterized in that: The red mud comprises the following components in percentage by mass: 3-20wt% SiO2, 2-8wt% CaO, 10-20wt% Al2O3, 3-10wt% Na2O, and the rest are other oxides.

5. The environmentally friendly green casting clay sand according to claim 1, characterized in that: α-starch is smaller than 140 mesh and has a gelatinization degree greater than 96%.

6. The environmentally friendly green casting clay sand according to claim 1, characterized in that: The particle size of the husk powder is less than 140 meshes, and the organic matter in the husk powder is greater than 80wt%.

7. The environmentally friendly green casting clay sand according to claim 1, characterized in that: The particle size of potassium acetate is less than 100 mesh and the purity is greater than 95%.

8. The environmentally friendly green casting clay sand according to claim 1, characterized in that: The purity of ethyl silicate is greater than 99%, and ethyl silicate is one or more of ethyl silicate 28, ethyl silicate 32, and ethyl silicate 40.

9. The method for preparing environmentally friendly green casting clay sand according to any one of claims 1 to 8, characterized in that: The steps include: a1. Add potassium acetate to water and stir to dissolve it; then add ethyl silicate and stir to obtain ethyl silicate hydrolyzate; a2. Add ethyl silicate hydrolyzate to silica sand and premix; a3. Add red mud, rare earth oxide powder and husk powder to the premix; a4. Then add sodium bentonite and α-starch to the mixture and mix thoroughly to obtain the environmentally friendly wet mold casting clay sand.

10. The method for preparing environmentally friendly green casting clay sand according to any one of claims 1 to 8, characterized in that: The steps include: b1. Add potassium acetate to water and stir to dissolve it; then add ethyl silicate and stir to obtain ethyl silicate hydrolyzate; b2. Mix red mud, rare earth oxide powder, rice husk powder, sodium bentonite, α-starch and silica sand; b3. Add the ethyl silicate hydrolyzate prepared in b1. and mix them to obtain the environmentally friendly wet mold casting clay sand.

Citation Information

Patent Citations

  • Anti-caking foundry molding sand and preparation method thereof

    CN104475656A

  • High-quality molding sand

    CN105903886A